2003
DOI: 10.1039/b211364c
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the short Pt–Tl bonds in model compounds [H5Pt–TlHn]n−

Abstract: RHF, DFT and MP2 calculations are reported for the compounds [H5Pt-TlHn]n-, n = 0-2. These serve as analogues for the experimentally known [(NC)5Pt-Tl(CN)n](n-)-species. The very short bond between platinum and thallium is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Previous experimental and theoretical studies have concluded that for the series I-V the oxidation states lie somewhere between Pt IV and Pt II and between Tl I and Tl III . 19,24,25 If we inspect the Hirshfeld charges in the various computational models (Table 3), obviously there is no resemblance to the oxidation states reported previously, but also not to their trends. For instance, for Tl the trend of increasing oxidation number deduced experimentally 19 is not visible in the calculated positive charges along the series.…”
Section: Pt and Tl Oxidation Statesmentioning
confidence: 88%
“…Previous experimental and theoretical studies have concluded that for the series I-V the oxidation states lie somewhere between Pt IV and Pt II and between Tl I and Tl III . 19,24,25 If we inspect the Hirshfeld charges in the various computational models (Table 3), obviously there is no resemblance to the oxidation states reported previously, but also not to their trends. For instance, for Tl the trend of increasing oxidation number deduced experimentally 19 is not visible in the calculated positive charges along the series.…”
Section: Pt and Tl Oxidation Statesmentioning
confidence: 88%
“…This and related systems have also been theoretically studied in Refs. [57,58]. In the latter work (model systems with CN -replaced by H -), the unusually short Pt-Tl distance of approx.…”
Section: Two-component Zora-dft Calculationsmentioning
confidence: 91%
“…The M-M' systems herein are akin to other systems shown in the literature with varying degrees of metal-metal distances and deviations in geometryone in particular showing rather strong Pt(II)-Tl(III) polar-covalent bonding in [(NC) 5 Pt-Tl(CN) n ] n -complexes discovered by Glaser and co-workers that possess short intramolecular M-M' distances; subsequent computational studies completed by Pyykkö and Patzschke supported the polar-covalent bond argument. [79,80] In Glaser's complexes, the Pt(II)-Tl(III) centers exhibit a difference in electronegativity with corresponding orbital energy mismatch, leading to a significant shortening of M-M' distances. For the closed-shell metal center complexes herein, on the other hand, d 10 All That Glitters Is Not Gold of the lighter metal center to the Au(I) organometallic center, leading to short intramolecular M-M' distances.…”
Section: Photophysical Propertiesmentioning
confidence: 99%